M, Kea Menegosiasikan Keadilan dalam Cerai Gugat (Perceraian yang Diajukan Istri): Pengalaman Perempuan di Pengadilan Agama Indonesia - Warnis; Martin Kustati; Nelmawarni; Syarifatul Hayati; Siti Atieqoh (Institut Agama Islam Negeri Curup, 2026)
The rising number of divorce cases in Indonesia reflects shifting gender relations within families and the dynamics of Islamic family law. Existing studies have largely focused on formal legal aspects or statistical trends, while limited attention has been given to how women articulate their gendered legal consciousness in the practice of wife‑initiated divorce (cerai gugat). This study addresses that gap by highlighting the novelty of analyzing gendered legal consciousness as a framework for understanding women’s agency in litigation. Using a qualitative case study design in three Religious Courts (Surabaya, Semarang, Bandung), data were collected through in‑depth interviews with 7–12 female petitioners and 5–7 court actors (judges, clerks, lawyers) in each site, complemented by courtroom and mediation observations. Purposive sampling with maximum variation was applied to capture diverse experiences based on grounds for divorce, socio‑economic background, and legal representation. Findings reveal that women strategically mobilize legal procedures and mediation to transform private issues—domestic violence, infidelity, neglect—into legally recognized claims. Although litigation imposes emotional and administrative burdens, participation in court provides new forms of empowerment and symbolic legitimacy. More importantly, women’s interactions with judicial processes shape gendered legal consciousness: they come to understand and reinterpret law as both a site of constraint and a space for renegotiating gender relations. Thus, litigation and mediation are not neutral mechanisms but arenas where agency is asserted and justice redefined. Theoretically, this research expands socio‑legal scholarship by situating gendered legal consciousness within Islamic family law. Practically, it demonstrates that Religious Courts function as dynamic social arenas where gender power relations are contested and women’s agency is reconstituted.